Urgensi Pendidikan Islam dalam Perspektif Al Qur’an: Studi Tafsir Surat At-Taubah Ayat 122 - Aski Fadhila Salsabilla; Sarwadi Sulisno (GLOBAL SCIENTS PUBLISHER, 2025)
Islamic education is an important means of shaping the character, morality, and personality of a knowledgeable and pious Muslim society. The Qur’an, as the primary source of Islamic teachings, contains educational values that are relevant to the challenges of contemporary life. One verse that emphasizes the urgency of Islamic education is Surat At-Tawbah verse 122, which presents the concept of tafaqquh fiddin, namely the obligation of a group of believers to deepen their religious knowledge and guide the community. This study aims to examine the urgency of Islamic education based on the interpretation of Surat At-Tawbah verse 122. The research employs a qualitative approach using library research methods through the analysis of the Qur’an, tafsir works, and relevant scholarly literature. The findings indicate that Islamic education represents a form of intellectual jihad that plays a strategic role in instilling faith-based values, cultivating noble character, and developing students’ spiritual intelligence.